Silvertree : a start-up for entrepreneurs by entrepreneurs? - Urban, Boris; Mitchell, Clare (London : Wits Business School, 2022)
It was May 2018, when Paul Cook, one of the three co-founders of Silvertree Holdings (Silvertree), a privately-owned investment holding and operating company focused on technology and consumer assets in sub-Saharan Africa, was preparing an update for shareholders. It was five years since he and his co-founders Manuel Koser and Peter Allerstorfer had started their business, with its payoff line "for entrepreneurs by entrepreneurs." As Cook reflected upon what the young company had achieved, he wondered how true it had been to this maxim.
Orginally Published InUrban, B., & Mitchell, C. (2019). Silvertree: A Start-up for Entrepreneurs by Entrepreneurs?. WBS-2019-7. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Case studies